2010
DOI: 10.1016/j.molcel.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The c-di-GMP Binding Protein YcgR Controls Flagellar Motor Direction and Speed to Affect Chemotaxis by a “Backstop Brake” Mechanism

Abstract: SUMMARY We describe a mechanism of flagellar motor control by the bacterial signaling molecule c-di-GMP, which regulates several cellular behaviors. E. coli and Salmonella have multiple c-di-GMP cyclases and phosphodiesterases, yet absence of a specific phosphodiesterase YhjH impairs motility in both bacteria. yhjH mutants have elevated c-di-GMP levels and require YcgR, a c-di-GMP-binding protein, for motility inhibition. We demonstrate that YcgR interacts with the flagellar switch-complex proteins FliG and Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
453
1
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(480 citation statements)
references
References 57 publications
16
453
1
10
Order By: Relevance
“…The applicability of DRa-CALA to high-throughput metabolite interactomics was demonstrated by screening for binding proteins of an important secondary signaling dinucleotide, cdiGMP. Recent findings have identified cdiGMP as the signaling molecule that controls biofilm formation, motility, and a number of other bacterial functions (2,3,(25)(26)(27). Although the enzymes known to synthesize and degrade cdiGMP are restricted to bacteria, there are questions as to which bacterial species express cdiGMP-binding proteins.…”
Section: Dracala Detection Of Cdigmp-binding Proteins In Diverse Pro-mentioning
confidence: 99%
“…The applicability of DRa-CALA to high-throughput metabolite interactomics was demonstrated by screening for binding proteins of an important secondary signaling dinucleotide, cdiGMP. Recent findings have identified cdiGMP as the signaling molecule that controls biofilm formation, motility, and a number of other bacterial functions (2,3,(25)(26)(27). Although the enzymes known to synthesize and degrade cdiGMP are restricted to bacteria, there are questions as to which bacterial species express cdiGMP-binding proteins.…”
Section: Dracala Detection Of Cdigmp-binding Proteins In Diverse Pro-mentioning
confidence: 99%
“…First, because cdiG is found naturally in E. coli, cdiG-specific phosphodiesterases exist for its breakdown (32). The presence of these phosphodiesterases, and the absence of cdiA-or cAG-specific phosphodiesterases, could have led to the lower observed levels of cdiG in the cell lysate.…”
mentioning
confidence: 99%
“…To alter gene expression or protein activity in response to external or internal signals, c-di-GMP interacts with several proteins (1,2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In addition, two classes of RNAs have been reported that bind this second messenger, the c-di-GMP-I (class I) and c-di-GMP-II (class II) riboswitches (18,19).…”
mentioning
confidence: 99%